Roman Lead ‘Iao Abrasax’ Amulets: Magical Pendants, Rings, and Beads - Boersema, Gert (KOINON: The International Journal of Classical Numismatic Studies, 2022)
The practice of magic was widespread in the Graeco-Roman world. Traces are found abundantly, both in literary sources and in material culture. Particularly well-known and surviving in large numbers are the magical hardstone gems bearing esoteric inscriptions and a range of imaginative imagery. The majority of these were set into the bezels of rings and worn as pendants. The largest number of magical gems can be dated to the late 2nd to 4th centuries and they are provenanced to virtually every part of the Roman empire. A class of lead objects consisting of magical pendants, rings and beads has not received much attention, even though they are clearly related to the hardstone gems and were likely used as their substitutes. This paper and the catalogue below will serve to fill at least part of this lacuna. The catalogue distinguishes 110 different amulet moulds and records a corpus of 190 lead amulets.